acunningham19
New member
- Joined
- Apr 11, 2013
- Messages
- 6
ab^cx+d=h
We have x=log(h-k)/a, divided by C log(b)
are we correct
We have x=log(h-k)/a, divided by C log(b)
are we correct
Maybe. You didn't start out with a 'k' and your exponent is not clear. If you mean \(\displaystyle e^{cx}\), you should include parentheses in order to be better understood. e^(cx)
Then hopefully the first two steps are obvious: subtract K from both sides: ab^(cx+ d)= h- Ksorry i typed it fast it should be ab^(cx+d) +K=h
Then hopefully the first two steps are obvious: subtract K from both sides: ab^(cx+ d)= h- K
Divide both sides by a: b^(cx+ d)= (h- K)/a
Now, the "inverse" of an exponential is the logarithm. Take the logarithm of both sides (whatever base you want).
What do you get then?